Altering the binding properties of PRDM9 partially restores fertility across the species boundary - Davies, B; Gupta Hinch, A; Cebrian-Serrano, A; Alghadban, S; Becker, PW; Biggs, D; Hernandez-Pliego, P; Preece, C; Moralli, D; Zhang, G; Myers, S; Donnelly, P (Oxford University Press, 2021)
Sterility or subfertility of male hybrid offspring is commonly observed. This phenomenon contributes to reproductive barriers between the parental populations, an early step in the process of speciation. One frequent cause of such infertility is a failure of proper chromosome pairing during male meiosis. In subspecies of the house mouse, the likelihood of successful chromosome synapsis is improved by the binding of the histone methyltransferase PRDM9 to both chromosome homologs at matching positions. Using genetic manipulation, we altered PRDM9 binding to occur more often at matched sites, and find that chromosome pairing defects can be rescued, not only in an intersubspecific cross, but also between distinct species. Using different engineered variants, we demonstrate a quantitative link between the degree of matched homolog binding, chromosome synapsis, and rescue of fertility in hybrids between Mus musculus and Mus spretus. The resulting partial restoration of fertility reveals additional mechanisms at play that act to lock-in the reproductive isolation between these two species.